Windows to the sold: verbo-visual multimodality in storefront windows. Issue 5 (10th April 2020) - Lick, Erhard; Bargenda, Angela; Trabelsi, Dhoha
Abstract : Purpose: The article seeks to enrich the body of research on store atmospherics by identifying how storefront window design impacts store entry decisions. An innovative multimodal design approach is presented, considering both visual and verbal constituents. Design/methodology/approach: Study 1 draws on a corpus of high-end storefront windows to create a categorization regarding different levels of verbo-visual complexity. The survey in Study 2 ( n  = 234) serves two purposes: first, to confirm these levels of complexity and second, to investigate the relation between the complexity of window design and store entry decisions. Findings: Study 2 confirms the order of complexity established in Study 1. The results reveal an inverted-U relationship between window complexity and store entry propensity. Windows of medium level of complexity produce shoppers' relatively highest store entry propensity. Practical implications: The findings suggest that retailers would benefit from adopting verbo-visual window designs of medium complexity, as this combination optimizes the likeliness of consumers to enter stores. Originality/value: Research on store atmospherics has until recently primarily focused on in-store cues. Studies on store windows remain vastly underrepresented in extant scholarship. The article not only fills this gap but also incorporates an original interdisciplinary angle on multimodality, which offers new methodological perspectives for research in retail and distribution scholarship.